AI-Powered Cybersecurity in Agile Workflows: Enhancing DevSecOps in Cloud-Native Environments through Automated Threat Intelligence (Journal of Science & Technology, 2020)
In the rapidly evolving landscape of cloud-native environments, the integration of artificial intelligence (AI) into cybersecurity frameworks has emerged as a critical strategy for enhancing security measures within Agile workflows. This paper delves into the application of AI technologies to bolster cybersecurity, specifically focusing on automated threat intelligence and the principles of DevSecOps. As organizations increasingly adopt Agile methodologies for software development, the need to incorporate security practices into the DevOps pipeline becomes paramount. By leveraging AI-driven approaches, organizations can streamline their security operations, facilitate proactive threat detection, and enhance the overall resilience of their cloud-native architectures.